Effect of annealing on the structural, microstructural and optical properties of co-evaporated Cu2SnS3 thin films. (July 2015) - Chalapathi, U.; Jayasree, Y.; Uthanna, S.; Sundara Raja, V.
Abstract: The effect of annealing temperature and duration on the growth and properties of Cu2 SnS3 films, deposited by co-evaporation of elemental Cu, Sn and S onto soda-lime glass substrates held at 350 °C is investigated. X-ray diffraction and Raman spectroscopy studies were used for phase identification. The as-deposited films are multi-phase containing Cu2 SnS3 and the secondary phases Cu4 SnS4, Cu1.9375 S & SnS. Films annealed at 550 °C and 580 °C under sulfur atmosphere are found to be monoclinic Cu2 SnS3 with minor Cu1.9375 S. The direct optical band gap and optical absorption coefficient of monoclinic Cu2 SnS3 phase are found to be 0.86 ± 0.03 eV and >10 4  cm −1 respectively. The electrical resistivity of the films is found to be in the range 0.02−0.35 Ω-cm depending on the annealing conditions. Highlights: Growth of Cu2 SnS3 thin films by co-evaporation. Effect of annealing temperature on the properties of co-evaporated films. X-ray diffraction, micro-Raman and optical analyses for phase identification.